Executive disadvantages in the layered wall of the facade = Wady wykonawcze w trójwarstwowej ścianie elewacyjnej - Grochowska, Elżbieta; Matysiak, Antoni (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this paper a case of three-layer wall and fitting windows is described. The walls outside layer are made of clinker brick. The public basis is a situation, which occurred in an office building. In this building was a water stain on the windows inside the upstairs part the building, during the rain. In project of the building there were no details of performing three-layer wall and fitting of windows. In Poland one did not described in detail the realization for windows installation in three-layer wall.
Keywords: ściana trójwarstwowa; osadzenie okien; wady wykonawcze; projekt budowlany; three-layer wall; fit windows; defect regulations; building project